Effects of different exercise modalities on inflammatory markers in the obese and overweight populations: unraveling the mystery of exercise and inflammation - Guo, Yongqing; Qian, Haonan; Xin, Xianyang; Liu, Qinlong (Frontiers in Physiology, 2024)
In the realm of obesity and overweight, the risk of chronic diseases significantly escalates, closely intertwined with inflammatory factors. Research suggests that specific exercise interventions, particularly aerobic exercise and resistance exercise, can have beneficial effects on inflammation levels. However, debates persist regarding the actual impact of exercise in the obese and overweight population. We employed meta-analysis research methods and searched the China National Knowledge Infrastructure (CNKI), Wanfang Data, PubMed, and Web of Science databases to gather controlled experiments on the effects of resistance exercise or aerobic exercise on C-reactive protein (CRP), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α). Two researchers independently conducted literature screening and data extraction. The quality of the literature was assessed according to the Cochrane Handbook standards, and subgroup analyses of CRP, IL-6, and TNF-α were performed using RevMan 5.4 software [1] . Through quantitative synthesis of results from 22 selected studies encompassing a total of 1135 research subjects, this study systematically explored the specific regulatory effects of different exercise modalities on inflammatory markers in the obese and overweight population. The findings indicate that both aerobic exercise and resistance exercise effectively reduce CRP levels in obese individuals, with aerobic exercise demonstrating a more pronounced effect. Aerobic exercise also significantly lowers IL-6 levels, while the impact of resistance exercise on IL-6 is relatively minor. However, in terms of reducing TNF-α levels, neither modality appears to exert a significant effect. Overall, exercise, especially aerobic exercise, emerges as a positive regulator of inflammatory markers in the context of obesity and overweight.